Constitutional regulation of the legislative competence of provincial councils in Iraq - Samer Hameed Safar (Eximia, 2024)
This study aims to highlight the constitutional legitimacy of local laws issued by the governorate councils under Law No. 21 of 2008, which are not related to a specific region. These entities began to issue local laws after the recent amendments under the 2005 Constitution, based on the principle of separation of powers and using the analytical approach. Through analyzing the legal texts of the Iraqi Constitution and the laws of the governorates, the study concluded that these legislations issued by these councils are unconstitutional. The study provides recommendations aimed at correcting the course of legislators and addressing the defects that may affect democracy regarding the work of those councils and their response to the legislative process. The Iraqi Parliament should handle the legislation since the purpose of these councils is to satisfy the local needs of the governorates that are not organized into regions, as stipulated by the Iraqi Constitution for the year 2005, especially after the transformation of the Iraqi state into a democratic system. The study concluded that the local councils need to amend their law to keep up with the political developments that Iraq and the world are witnessing, in particular.